Factors That Affect Employment Outcomes Among Transition-age Adolescents With Vision Impairment: a Systematic Literature Review - Tommy Firmanda (Indonesian Journal of Disability Studies, 2018)
Introduction: This study aims to identify and synthesise the study of employment outcomes in the transition to adulthood for young people with visual impairment. Methods: The PRISMA Statement Protocol is used as a guide in conducting a systematic review of the literature, including the criteria for choosing a study, a search strategy, and a synthesis of findings. Results: Seven studies of factors influencing post-high school employment outcomes among adolescent transition-age with visual impairment were identified. Six studies used data from National Longitudinal Transition Study 2 (NLTS2), and one study using RSA Case Service Report (RSA-911). Of the seven studies with quantitative design, only one study is a correlational study. All studies reported a significant relationship and influence between work-related factors and post-secondary education employment outcomes. 13 factors affect positively and only 1 factor that has a negative influence. Discussion: Among the 13 factors, eight factors confirm the results of previous studies. While the other five factors still need to be investigated further, although in this study the five factors have a great potential as a predictor of successful work of youth with visual impairment. Limitations of data sources need to be a concern in conducting future studies. Implications for practitioners: The high unemployment rate in this population indicates a lack of evidence-based research in this area. Educational practitioners encouraged to evaluate intervention programs to improve the success of the transition-age youths with vision impairment and publish the findings for later can be use as a basis for developing appropriate livelihood policies and education programs.